2023
DOI: 10.3390/coatings13030575
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Nano-Silver–Silver Ion Composite Antibacterial Agents for Green Powder Coatings

Abstract: Nano-silver is characterized by broad-spectral, strong and stable antibacterial properties, which make it a promising material in coating applications. However, the efficiency of nano-silver is generally low in the coating of films. Here, we developed a series of highly active and durable silver ions–nano-silver antimicrobial agents for powder coatings. To optimize antimicrobial activity and durability, two different nano-silver generation methods, i.e., in situ and ex situ methods combined with different carr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Carrier materials should have some important parameters, including unique characteristics in cation exchange capacity and pore structure, as these aspects influence the function of the active components. It is widely reported that zeolite-and clay-based materials can serve as carriers for silver ions [12][13][14]. Zeolite carriers possess a framework of silicate with high adsorption and ion exchange capabilities, which permits them to act as inorganic reservoirs for silver ions [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Carrier materials should have some important parameters, including unique characteristics in cation exchange capacity and pore structure, as these aspects influence the function of the active components. It is widely reported that zeolite-and clay-based materials can serve as carriers for silver ions [12][13][14]. Zeolite carriers possess a framework of silicate with high adsorption and ion exchange capabilities, which permits them to act as inorganic reservoirs for silver ions [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%